Contraception provision in the postpartum period: Knowledge, views and practices of midwives. Issue 1 (February 2021) - Botfield, Jessica R.; Tulloch, Melanie; Contziu, Hannah; Phipps, Hala; Bateson, Deborah; Wright, Sarah M.; McGeechan, Kevin; Black, Kirsten I.
Abstract: Background: Women are susceptible to unintended pregnancies in the first year after giving birth, particularly as consideration of contraception may be a low priority during this time. Discussing and providing contraception before women leave hospital after giving birth may prevent rapid repeat pregnancy and its associated risks. Midwives are well placed to assist with contraceptive decision-making and provision; however, this is not routinely undertaken by midwives in the Australian hospital setting and little is known regarding their views and experiences in relation to contraception. Methods: An anonymous survey was conducted with midwives at two urban hospitals in New South Wales to better understand their contraceptive knowledge, views and practices regarding midwifery-led contraception provision in the postpartum period. Findings: The survey was completed by 128 midwives. Most agreed that information about contraception provided in the postpartum period is valuable to women, although their knowledge about different methods was variable. The majority (88%) believed that midwives have a role in providing contraceptive information, and 79% reported currently providing contraceptive counselling. However, only 14% had received formal training in this area. Conclusion: Findings demonstrate that most midwives provide some contraception information and believe this is an important part of a midwife's role. Yet most have not undertaken formal training in contraception. Additional research is needed to explore the content and quality of midwives' contraception discussions with women. Training midwives in contraceptive counselling would ensure women receive accurate information about available options. Upskilling midwives in contraception provision may increase postpartum uptake and reduce rapid repeat pregnancies.